LEGAL RESEARCH METHODS: APPROACHES, EFFICIENCY, AND BEST LEGAL PRACTICES - Jorovlea, Elvira; Tudor, Pașcaneanu (SWorldJournal, 2025)
Legal research methods combine traditional approaches with modern digital tools for maximum efficiency. Classical techniques include case law analysis, statutory interpretation, and secondary source utilization. Digital platforms provide rapid access to l